AN EXPLORATION OF SRI LANKA’S TROPICAL ENVIRONMENT THROUGH PRIMARY SCHOOL SCIENCE EDUCATION - Prashant S. Mothe (SMART: Journal of Multidisciplinary Educational, 2025)
This study aims to explore the integration of Sri Lanka’s tropical environment into primary school science education to enhance students’ scientific reasoning, environmental literacy, and engagement. The research employs a literature-based methodology, systematically reviewing recent empirical studies, curriculum documents, and educational reports to synthesize existing knowledge, identify gaps, and propose context-rich, place-based instructional strategies. Data analysis involved thematic coding of teacher practices, curriculum integration, and student learning outcomes, with findings summarized in tables and visualized in Figure 2 to illustrate patterns of engagement, observational skills, conceptual understanding, and environmental awareness. Results indicate that while primary school teachers recognize the value of local environmental contexts, actual classroom implementation remains limited due to insufficient professional development, resource constraints, and content-driven curricula. Nevertheless, the review demonstrates that even partial integration of tropical ecosystems significantly improves students’ inquiry skills, conceptual understanding, and environmental attitudes. The novelty of this study lies in its focus on primary education within tropical island contexts, combining curriculum alignment, teacher professional development, and ecosystem-based learning into a coherent instructional framework, which is largely absent in previous literature. Additionally, this research develops a validated instrument for assessing student outcomes in place-based science learning, offering both conceptual and practical contributions. The findings emphasize the importance of experiential, context-driven learning and provide a scalable model for enhancing science education in biodiverse regions. In conclusion, integrating local tropical ecosystems into primary science curricula not only improves cognitive and affective learning outcomes but also fosters environmental stewardship and a sense of place, offering practical implications for educators, curriculum designers, and policymakers in Sri Lanka and other tropical contexts.